Ujaran Kebencian Anak di Media Sosial : Tantangan Penegakan Hukum dalam Sistem Peradilan Pidana Anak - M Anlian Fanza Ghifari; Rini Fathonah; Muhammad Farid (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rise in hate speech cases involving minors on social media has become a pressing legal issue in the digital era. As more children engage with online platforms, the risks of harmful behaviors such as hate speech have grown, presenting challenges for legal systems worldwide. This study aims to examine the enforcement of law against children who commit hate speech crimes on social media, with a focus on understanding both the legal processes and the obstacles encountered during enforcement. Using a combination of normative and empirical juridical approaches, the study collects data through interviews with law enforcement officials in Bandar Lampung. The findings indicate that, although the juvenile justice system emphasizes restorative justice and provides diversion mechanisms for minor offenders, the practical application of these principles remains insufficient. Key technical challenges, such as difficulties in tracking accounts and the ease with which digital evidence is deleted, pose significant barriers to effective prosecution. Additionally, structural issues, including limited resources and the lack of digital legal literacy among law enforcement, exacerbate the problem. Despite these challenges, the study identifies best practices in diversion, such as involving psychologists, probation officers, and community leaders, as potential pathways to more humane and rehabilitative resolutions. Furthermore, the study highlights the importance of strengthening coordination between agencies, improving law enforcement capacity in digital forensics, and implementing early digital literacy education. These efforts are crucial for creating a more effective legal framework to address hate speech cases committed by children on social media, ensuring both justice and rehabilitation in the digital age.